Pelatihan Membaca Cepat dengan Teknik Skimming melalui Layanan Penguasaan Konten - Syarifah Aini Rambe (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2022)
Speed ​​reading training conducted in the village of Reje Guru is a service activity that aims to increase adolescent reading interest and help teenagers quickly understand the contents of the books they have read. This activity uses skimiing techniques through content mastery services. This training is carried out for 30 days and is carried out in 2 ways, namely directly and indirectly. The result of this activity is that teenagers increase their interest in reading and are able to quickly understand the contents of the books they read.